Avaliação microbiológica de solo no cultivo de soja e milho em sucessão a adubos verdes de inverno - Vanelli, Jaqueline (2016)
The succession of crop plants can influence the soil microbial community, with direct effects on plant production. This work aimed to evaluate the microbial diversity of fungi, bactaria and nematode of soil for different species of green manure (Avena strigosa, Urochloa ruziziensis, Pisum sativum and Lupinus albus) of winter and sampling time as well as 60 days after the cultivation of soybeans and corn in succession. To evaluate the population density of these organisms and estimate the carbon and nitrogen of microbial biomass, an experiment was conducted in two stages. In the first one there was the planting of different species of green manure, and in the second the sowing of two crops: soybean and corn in succession. The experiment in the cultivation of green manure was completely randomized (DBC). For the experiment of summer crops was used a randomized complete block design (DBC) with split plots. The principal plot consisted of green winter fertilizers, and the subplots the corn and soybean. Samples were collected at 0, 60, 90, 120 and 150 days of cultivation of winter crops. In the area with soybean and corn the samples were performed 60 days after sowing the crop. The results showed that Brachiaria had the less production of dry biomass among green manures. The nematode density, mycorrhizal fungi, bacteria and pathogenic fungi; as well as microbial biomass and nitrogen were not affected by the species of green manure. There was a significant effect of sampling time to non-pathogenic nematodes with the highest population in 90 days. The cultivation of soybean and corn did not influence the number of non-pathogenic nematodes, but influenced the number of mycorrhizal fungi. The highest total number of mycorrhizal fungi Glomus macrocarpum and Gigaspora margarita were found under corn crop. The estimated values of carbon and nitrogen of microbial biomass were not affected by the species of green manures, and also had no effect on crops in succession. There was no statistical difference between fungi and bacteria to any of the variables. There was the constant presence of fungi of the genus Penicillium, Aspergillus and Fusarium